2007
DOI: 10.1111/j.1365-2044.2007.04934.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of skin surface warming on pre‐operative anxiety in neurosurgery patients*

Abstract: SummarySkin surface warming of patients not only improves thermal comfort, but has been shown to reduce anxiety in a pre-hospital setting. We tested the hypothesis that pre-operative warming can reduce pre-operative anxiety as effectively as a conventional dose of intravenous midazolam in patients undergoing neurosurgery. We randomly allocated 80 patients to four groups in the pre-operative holding area. Treatment was applied for 30-45 min with (1) passive insulation and placebo; (2) passive insulation and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 63 publications
2
12
0
1
Order By: Relevance
“…A large proportion of our study cohort were anxious, with 50% having APAISa ≥ 10, which is similar to other studies of neurosurgical patients; Perks et al found 55% of their patients had a pre-operative APAISa score ≥ 10 [8]. The overall mean STAI scores were also similar to other neurosurgical studies [15,16], suggesting our cohort is representative of the neurosurgical patient population. The high anxiety levels were present despite the patients having already been seen and assessed by both their caring anaesthetist and surgeon, which has previously been shown to decrease pre-operative anxiety [3,17,18].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A large proportion of our study cohort were anxious, with 50% having APAISa ≥ 10, which is similar to other studies of neurosurgical patients; Perks et al found 55% of their patients had a pre-operative APAISa score ≥ 10 [8]. The overall mean STAI scores were also similar to other neurosurgical studies [15,16], suggesting our cohort is representative of the neurosurgical patient population. The high anxiety levels were present despite the patients having already been seen and assessed by both their caring anaesthetist and surgeon, which has previously been shown to decrease pre-operative anxiety [3,17,18].…”
Section: Discussionsupporting
confidence: 88%
“…Median APAISa level in the acupuncture group, but not in the control group: 10 (6-13 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]) to 7 (4-10 [4-18]), p < 0.001 vs. 9 (6-13 [4-18]) to 8.5 (6-12 [4-18]), p = 0.872, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Thermal comfort in our prewarmed patients increased from 50 mm to 60 mm on a 100-mm scale, whereas core temperature only increased 0.2°C. Previous work has similarly shown that prewarming increases the sensation of warmth and that warming per se does not reduce anxiety [27].…”
Section: Discussionmentioning
confidence: 90%
“…13 This is a validated tool for self-reporting anxiety, already used during the perioperative period. [1][2][3]14 It comprises 2 sets of 20 statements.…”
Section: Assessment Of Anxietymentioning
confidence: 99%